Electromigration techniques : theory and practice - Dziubakiewicz, Ewelina; Szumski, Michal; Buszewski, Boguslaw (Springer Series in Chemical Physics, 2013)
The book provides the broad knowledge on electromigration techniques including: theory of CE, description of instrumentation, theory and practice in micellar electrokinetic chromatography, isotachophoresis, capillary isoelectric focusing, capillary and planar electrochromatography (including description of instrumentation and packed and monolithic column preparation), 2D-gel electrophoresis (including sample preparation) and lab-on-a-chip systems. The book also provides the most recent examples of applications including food, environmental, pharmaceutical analysis as well as proteomics.